2017
DOI: 10.1021/acs.jpcc.7b05090
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Investigation of Thermal Regeneration of High-Silica ZSM-5 Zeolite through in Situ Synchrotron X-ray Powder Diffraction and Adsorption Studies

Abstract: Adsorption is important for many applications including catalysis and water remediation technology. To improve the performances of such applications, it is essential to have a deep understanding of adsorbent−adsorbate interactions, and of the dynamics involved in adsorption/desorption processes of porous adsorbent materials. In this study, the thermal desorption of high-silica (HS) ZSM-5 zeolite loaded with mixtures of organic compounds (namely, methyl tert-butyl ether/toluene, and methyl tert-butyl ether/1,2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…As reported in previous works, ,,, within the stability field of the monoclinic phase (i.e., for T < T c ), no changes in the extraframework site occupancies are observed. Specifically, under the assumption of guest organic molecules exclusively localized within the host ZSM-5 zeolite framework, it has been observed that up to the transition temperature the number of guest molecules per unit cell is almost unchanged with respect to that found at RT.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…As reported in previous works, ,,, within the stability field of the monoclinic phase (i.e., for T < T c ), no changes in the extraframework site occupancies are observed. Specifically, under the assumption of guest organic molecules exclusively localized within the host ZSM-5 zeolite framework, it has been observed that up to the transition temperature the number of guest molecules per unit cell is almost unchanged with respect to that found at RT.…”
Section: Resultssupporting
confidence: 77%
“…According to those investigations, ,,, the first DTG peak can be ascribed to the desorption of species bounded to the sample surface (water molecules and/or embedded organic species). On the contrary, the desorption of guest molecules embedded in the ZSM-5 channels occurs at higher temperature, and their mobility inside the framework is controlled by configurational effects .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon is further established with negative values of ΔGo. At higher temperature, Gibbs free energy changed from negative to positive, this suggested that desorption took place [63]. Besides, disorderliness at TA-poly(AN- co -AA) adsorbent-adsorbate solution interface decreases during adsorption process as indicated by the values of ΔS0.…”
Section: Resultsmentioning
confidence: 96%